Burgäschisee 5000-3000 v. Chr. Siedlungsdynamik und Mobilität, Landnutzung und Subsistenz - Hafner, Albert; Hostettler, Marco (Open Series in Prehistoric Archaeology, 2022)
Lake Burgäschi is a small lake on the Swiss Plateau, which has been inhabited since the Mesolithic, but is best known for its Neolithic lakeside settlements. Archaeological research has been conducted at Lake Burgäschi for the last 170 years, undergoing all the developments to modern archaeology. Recently, Lake Burgäschi has been re-explored as part of an interdisciplinary research project under the direction of the Institute of Archaeological Sciences at the University of Bern. Excavations were carried out at various sites around Lake Burgäschi, allowing for a new precise chronological classification of already known sites, but also revealing previously unknown settlement sites on the lakeshore. Furthermore, by means of interdisciplinary investigations on the pottery, animal and human bones as well as flint artefacts, previous knowledge on subsistence, mobility and land-use has been substantially extended. The present volume closes a long lasting research gap and combines new results with ancient data to a comprehensive synthesis.